Lack of confidence, the zero lower bound, and the virtue of fiscal rules - Sebastian Schmidt (European Central Bank (ECB), 2015)
In the presence of the zero lower bound, standard business cycle models with a Taylor-type monetary policy rule are prone to equilibrium multiplicity. A drop in confidence can drive the economy into a liquidity trap without any change in fundamentals. Using a prototypical sticky-price model, I show that Ricardian fiscal spending rules that prevent real marginal costs from declining in the face of a confidence shock insulate the economy from such expectations-driven liquidity traps.
Keywords: E52; E62; 330; government spending; liquidity trap; multiple equilibria; Ricardian fiscal policy; sunspots